Cohesiveness of Farmers’ Groups in Delta State Nigeria: Its Implication for Agricultural Development - Ofuoku , Albert Ukaro (Asian Journal of Agriculture and Rural Development, 2020)
This study which covered Delta State, Nigeria was embarked on to ascertain the cohesiveness of farmers’ groups and fathom the implications for agricultural development. At the first stage, 18 farmers associations were randomly selected from the list of farmers’ groups at the zonal headquarters of DTADP. Ten percent often membership strength of each selected association was randomly selected to form the study sample and this resulted to selection of 156 farmers. Farmers subscribed to the various groups for the purpose of accessing extension services/information and credit facilities. They also had the purpose of benefiting from government farmers’ empowerment schemes and exchange ideas, knowledge and information with other members of their respective groups. Most of the groups were found to be highly cohesive and members were also highly cohesiveness of the groups was influenced by members of satisfaction with the groups satisfied with their various groups. This implies that agricultural development and revival of the economy can be achieved. It is recommended that sustained cohesion of the groups should be encouraged through agricultural extension agents and other farmers should be encouraged for their specialized groups in other to reap benefits of self-help farmers’ groups.